Urotensin-II-Targeted Liposomes as a New Drug Delivery System towards Prostate and Colon Cancer Cells - Zappavigna, Silvia (J Oncol, 2019)
Urotensin-II (UT-II) and its receptor (UTR) are involved in the occurrence of different epithelial cancers. In particular, UTR was found overexpressed on colon, bladder, and prostate cancer cells. The conjugation of ligands, able to specifically bind receptors that are overexpressed on cancer cells, to liposome surface represents an efficient active targeting strategy to enhance selectivity and efficiency of drug delivery systems. The aim of this study was to develop liposomes conjugated with UT-II (LipoUT) for efficient targeting of cancer cells that overexpress UTR. The liposomes had a mean diameter between 150 nm and 160 nm with a narrow size distribution (PI ≤ 0.1) and a doxo encapsulation efficiency of 96%. Moreover, the conjugation of UT-II to liposomes weakly reduced the zeta potential. We evaluated UTR expression on prostate (DU145, PC3, and LNCaP) and colon (WIDR and LoVo) cancer cells by FACS and western blotting analysis. UTR protein was expressed in all the tested cell lines; the level of expression was higher in WIDR, PC3, and LNCaP cells compared with LoVo and DU145. MTT cell viability assay showed that LipoUT-doxo was more active than Lipo-doxo on the growth inhibition of cells that overexpressed UTR (PC3, LNCaP, and WIDR) while in LoVo and DU145 cell lines, the activity was similar to or lower than that one of Lipo-doxo, respectively. Moreover, we found that cell uptake of Bodipy-labeled liposomes in PC3 and DU145 was higher for LipoUT than the not-armed counterparts but at higher extent in UTR overexpressing PC3 cells (about 2-fold higher), as evaluated by both confocal and FACS. In conclusion, the encapsulation of doxo in UT-II-targeted liposomes potentiated its delivery in UTR-overexpressing cells and could represent a new tool for the targeting of prostate and colon cancer.